2019
DOI: 10.3390/reports2020016
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Tramadol are Prevalent among the First Episode Drug-Induced Psychosis in the Egyptian Population: Single Center Experience

Abstract: (1) Background: Cannabis and tramadol are featuring prominently in Egypt; however, their prevalence in first episode psychosis is still uncertain. We aimed at determining the prevalence of cannabis and tramadol among the first-psychotic episode in Egyptian inpatients and to compare the demographic and psychopathological profiles of substance abusers versus patients with the comorbid diagnosis. (2) Methods: Patients presented with psychotic episode and admitted to Mansoura Psychiatric Department were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In the present study, cannabinoids were the prevalent substance (46.3%) used followed by multiple drugs (36.6%) and opioids (9.6%). These findings were consistent with various studies conducted in the UK [17], Australia [18], and Canada [19] where cannabis besides alcohol was a commonly used substance. Compared to other substances, alcohol was less prevalent in psychotic disorder patients due to religious and cultural disapproval among ethnic groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, cannabinoids were the prevalent substance (46.3%) used followed by multiple drugs (36.6%) and opioids (9.6%). These findings were consistent with various studies conducted in the UK [17], Australia [18], and Canada [19] where cannabis besides alcohol was a commonly used substance. Compared to other substances, alcohol was less prevalent in psychotic disorder patients due to religious and cultural disapproval among ethnic groups.…”
Section: Discussionsupporting
confidence: 93%
“…Patterns of substance use appear to have a substantial part of individuals prior to the onset of psychotic disorders, possibly as early as first signs of illness [15]. There have only been a few large-scale studies of drug-induced psychosis where the incidence rates of alcohol and drug abuse ranged from 3% to 35% and 6% to 44%, respectively [16,17]. However, no study assessing the incidence of substance use in drug-induced chronic psychiatric patients has been conducted so far in our country.…”
Section: Introductionmentioning
confidence: 99%
“…Taha and colleagues in 2019 held a study on patients who presented with psychotic episode and admitted to Mansoura Psychiatric Department, they found that 66.7% of the studied patients had between 1-5 years self-reported histories of substance abuse predating the first psychotic episode [6]. That's to say, drug abuse may share a common genetic predisposition along with psychotic disorders, in which an increased probability for an individual to abuse substances and concomitantly or eventually tend to develop psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, drug abuse became an alarming problem in the last years that continue to cause national and societal concern [5]. In 2018, the Egyptian Ministry of Social Solidarity declared that substance abuse rates in Egypt surpassed 10% and doubled the global average and that tramadol was the commonest abused substance followed by cannabis and heroin [6].…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to a lack of capacity for data collection and analysis[ 64 ]. In Egypt, there are reports that substance abuse rates are as high as 10%-20% the global average, with cannabis and tramadol being the most abused substances[ 65 ]. In Tunisia, an increase in the trafficking and consumption of psychoactive substances have been observed since the political uprising that occurred in 2011[ 66 ].…”
Section: Epidemiology Of Substance Use Across the African Continentmentioning
confidence: 99%